“Born to Give Us Second Birth”: A Feminist Rediscovery of the Original Nicene Creed - Durber, Susan (International review of mission, 2025)
The article recounts a journey from wariness of the Nicene Creed and critique of its patriarchal origins to a rediscovery of the subversive potential of its original drafting at the Council of Nicaea. The Nicene Creed from 325 CE (later extended to become the Nicene-Constantinopolitan Creed in 381 CE) is deeply incarnational, with an understanding of salvation that is rooted in birth. The later creed dilutes this emphasis through its additions, and translations of both into English have obscured the radical message that in Christ God became human (not only man) for all humankind. This article takes the original Nicene statement seriously and interprets Christianity as a faith of natality and incarnation rather than, as in much Western Christianity, of the cross. It reinterprets Nicaea through feminist philosophy, uncovering a more original reading. It suggests that since the celebration of Christmas moves hearts in even secular Europe, such a reading provides an opening for mission today.